Serum IL-17 levels correlate with urinary albumin in systemic lupus erythematosus (SLE) pregnant mice model - Wahyuni, Sari; Pratiwi, Agustina Ida; Mawaddah, Sofia; Iswati, Retno Setyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Women of reproductive age are more likely to have systemic lupus erythematosus (SLE), which frequently results in health issues, particularly during pregnancy. A normal pregnancy's first trimester shows a marked increase in the percentage of Th17 cells, which then steadily declined in the second and third trimesters. Meanwhile, IL-17 level increases in SLE-affected pregnant women. This study aimed to analyze the correlation between serum IL-17 and pregnancy outcome (fetus weight, blood pressure, urinary albumin) in SLE pregnant animal models. Twenty mice were randomly divided into two groups, including the normal pregnant group and SLE-pregnant group. The SLE pregnant mice was made by intraperitoneally induction of 0.5 mL pristane. Serum IL-17 was assayed by enzyme-linked immunosorbent assay (ELISA) method. The serum IL-17 level, the blood pressure and urinary albumin were significantly higher in the SLE pregnant mice group than those of the normal pregnant group (p< 0.05). The weight of fetus was significantly smaller in the group of SLE pregnant mice group than the normal pregnant group (p< 0.05). There was a significantly positive correlation between the serum IL-17 level and urinary albumin (p = 0.042; r = 0.459). In conclusion, serum IL-17 levels correlate with urine albumin in SLE pregnant models, but do not correlate with fetus weight and blood pressure.